Neglected scenario of sanitation in schools of Sunsari district of Nepal: Critical sphere for public health consideration (Health Renaissance, 2017)
Background: Provision of adequate water supply, sanitation facilities, hygiene and waste management in schools reduces the disease burden among children, staff and their families. Every child has equal right to grow in a safe and sound environment. However, levels of water supply, sanitation and hygiene are unacceptable in many schools worldwide.Method: Study included forty schools comprising twenty public and twenty private schools of Sunsari district selected by simple random sampling method. The status of school environment and sanitation were assessed by using observation and interview method using observation checklist, questionnaires and photographs.Result: Two public schools were completely devoid of sanitary facilities though toilet facility was present physically. Students couldn’t use toilet due to lack of water in one school due to theft of tube well and septic tank of the toilet was full in another school. Other remaining schools didn’t have satisfactory, clean and proper sanitary facilities. Only few schools had convenient hand washing point.Conclusion: Sanitation facilities were in neglected state evidenced by unavailability of sanitation facilities even though that was physically present and the sanitation facilities were in pitiable condition including cleanliness, water supply. All the stakeholders including school management, supervisors, parents, teachers, students should be ready to play vital role on their own. Lack of one toilet affects no. of students and people of surrounding area and raises of risk of soil transmitted diseases so this situation demands attention of authorities and other stakeholders.Health Renaissance 2015;13(2): 114-124